2015
DOI: 10.3389/fpsyg.2015.01578
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension and engagement in survey interviews with virtual agents

Abstract: This study investigates how an onscreen virtual agent's dialog capability and facial animation affect survey respondents' comprehension and engagement in “face-to-face” interviews, using questions from US government surveys whose results have far-reaching impact on national policies. In the study, 73 laboratory participants were randomly assigned to respond in one of four interviewing conditions, in which the virtual agent had either high or low dialog capability (implemented through Wizard of Oz) and high or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 63 publications
0
31
0
1
Order By: Relevance
“…The benefits for comprehension, according to the authors, are related to gestures and facial expressions affecting redundancy, which results in more learning. Conrad et al (2015) manipulated an agent’s dialog capability (high, low) and facial animation (high, low) and examined their effect on users’ comprehension and engagement in completing a survey. Answers to the survey were more accurate in response to agents with high capability dialog and these agents were judged as more personal and less distant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits for comprehension, according to the authors, are related to gestures and facial expressions affecting redundancy, which results in more learning. Conrad et al (2015) manipulated an agent’s dialog capability (high, low) and facial animation (high, low) and examined their effect on users’ comprehension and engagement in completing a survey. Answers to the survey were more accurate in response to agents with high capability dialog and these agents were judged as more personal and less distant.…”
Section: Discussionmentioning
confidence: 99%
“…Cue redundancy serves to reduce cognitive load (Stevens et al 2013). Conrad et al (2015) reported differential effects of facial animation and dialog capability moderated by context. The present results further corroborate such a relationship and point to the need to design agents and features in tandem with context and content.…”
Section: Discussionmentioning
confidence: 99%
“…The survey interviewing literature includes several studies demonstrating that CI reduces the bias in survey responses relative to SI (Schober and Conrad, 1997;Conrad and Schober, 2000;Schober et al, 2004Schober et al, , 2012Hubbard et al, 2012;Conrad et al, 2015;Bruckmeier et al, 2015). These studies have shown that, although CI can lead to longer interviews (potentially increasing costs), it can also improve respondents' comprehension of terms in survey questions that may be ambiguous with respect to the situations of particular respondents.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Conrad et al (2015) showed that small talk in survey interviewing to increase the users' comprehension and engagement. Bickmore and Cassell (2005) also used small talk to increase trust.…”
Section: Related Workmentioning
confidence: 99%